Cervical-Intracranial Atherosclerosis and Serum Uric Acid Level Association in Acute Stroke - EKİNCİ, GAZANFER; MİDİ, İPEK (GAZI UNIV, FAC MED, 2020)
Objective: We aimed to identify whether high uric acid levels were associated with atherosclerotic intracranial/extracranial arterial stenosis and atrial fibrillation (AF) and to determine if serum uric acid (SUA) levels were an independent risk factor. Methods: One hundred seventy-four patients who presented with acute stroke within 24 hours of onset and were admitted to our hospital between December 2016 and September 2017 were included in the study. Bamford classification was used for Stroke classification. The degree of vascular stenosis was classified as lumen contour irregularity, mild, moderate and severe stenosis using the The North American Symptomatic Carotid Endarterectomy Trial (NASCET) criteria. Results: The average age of 174 patients was 69 +/- 12.7 years. Elevated serum uric acid levels were found in 66 patients. The mean SUA level was 7.33 +/- 1.02 mg/dL in these patients. Thirty-six patients were examined with AF and 14 of these patients had high SUA levels. It was found that high SUA levels were mostly related with lacunar infarct (LACI) and partial anterior circulation infarct (PACI), respectively. High SUA levels were seen more commonly in the anterior circulation, especially in the extracranial part of the carotid artery, but this was not statistically significant (p>0.05). We found a statistically significant relation between high SUA levels in moderate and severe stenosis of the extracranial portion of the posterior circulation in women (p=0.01). There was a relationship between atrial fibrillation and extracranial atherosclerosis of the anterior circulation as contour irregularity and moderate stenosis (p=0.05). Conclusions: In our study, it was found that high SUA levels were related to LACI and PACI, respectively. Further studies with larger groups are needed.
Keywords: Stroke; Uric acid; Intracranial; Extracranial; Atherosclerosis; Atrial Fibrillation; MUSCLE-CELL-PROLIFERATION; CAROTID ATHEROSCLEROSIS; CARDIOVASCULAR-DISEASE; URATE; RISK; HYPERURICEMIA; HYPERTENSION; EVENTS